Cariprazine and clozapine combination for the treatment of psychosis in a young, female patient with schizophrenia: a case report - Dmuhovskis, Anzejs; Taube, Maris (Frontiers in Psychiatry, 2024)
The task of a psychiatrist is to select the most appropriate medication or combination of drugs to treat the symptoms of schizophrenia while minimizing the risk of side effects and ensuring the patient achieves the highest level of functioning possible. This is a challenging task as the action of each drug or group of drugs is different. The efficacy of cariprazine, which affects D3 receptors as a D3/D2 receptor partial agonist, has been extensively studied and is one of the first medication choices by practicing psychiatrists when treating patients with negative symptomatology. In this clinical case, we demonstrate the effective and safe treatment of a patient’s positive and affective symptoms using a combination of cariprazine, clozapine, and venlafaxine